Fungsi Keterangan Ahli Dalam Pembuktian Tindak Pidana Pembunuhan - Sherly Adam (JURNAL BELO, 2019)
The disclosure of a criminal case, especially the criminal act of pembuhunan very difficult, at least there are three things that can not be separated because it involves the validity or validity of a court decision, namely: a system of evidence embraced by procedural law, evidence and strength of evidence and evidence that will Strengthening the evidence presented in court. The function of expert information in the proving of murder offenses as evidence in the criminal justice process is required from the examination of the case both in the investigation process and in the court hearing is very important and necessary, especially to assist the investigator, prosecutor or judge in disclosing a case A very complex, complex assassination.